LABOR MARKET DYNAMICS AND IMPLICATIONS FOR ECONOMIC GROWTH - Ana Fitriyatul Bilgies; Nurjanna Ladjin; Alwinda Manao (Adisam Publisher, 2025)
Labor market dynamics play an important role in determining the direction and speed of a country's economic growth. Changes in the composition, skills and mobility of the workforce have significant implications for productivity, innovation and social welfare. Digital transformation and globalization have changed skills needs, created new demands in the job market and driven increased investment in education and training. The unemployment rate, wage structure, and social inclusion in the labor market also influence economic stability and income equality. Therefore, policies that support the creation of productive and inclusive jobs, as well as encouraging workforce mobility and adaptation to technological and economic changes, are crucial in ensuring sustainable economic growth. This study examines various factors that influence labor market dynamics and identifies strategic policies that can be implemented to maximize the contribution of the labor sector to economic growth.